Mapping the Distribution of Water Retention and Other Physical Properties of Soil on Intensive Agriculture Land in the Village Sumber Urip, Selupu Rejang District, Rejang Lebong Regency - Permata, Nathasya Vira; Hermawan, Bandi; Gusmara, Herry (BPFP Universitas Bengkulu, 2023)
This research aims to map water availability on intensively cultivated agricultural land so that the land management method will be carried out appropriately. The method used to determine the sample points was the stratified sampling method, and 31 soil sample points were obtained. Soil samples are analyzed for their physical properties, which include soil texture, total pore space, bulk density, permeability, potential of free energy, and water content. The analysis results are presented as an overlay map of the measured variables. The research results show that agricultural land on a slope of 0-15% with a total area of 233 ha has good soil water retention in terms of the physical properties of the soil, so there is no need to improve soil management. Agricultural land on a slope of 15-25% with an area of 79 ha requires additional treatment to increase water retention by adding soil amendments to increase total soil pore space. Agricultural land on a slope of 25-45% with an area of 124 ha has excellent soil water retention supported by soil conservation practices in making terraces and installing plastic mulch. Meanwhile, agricultural land on a slope of >45% with an area of 33 ha has poor soil water retention, so soil conservation practices are needed.